Mass collection of magnetotactic bacteria from the permanently stratified ferruginous Lake Pavin, France. (23rd March 2021) - Busigny, Vincent; Mathon, François P.; Jézéquel, Didier; Bidaud, Cécile C.; Viollier, Eric; Bardoux, Gérard; Bourrand, Jean‐Jacques; Benzerara, Karim; Duprat, Elodie; Menguy, Nicolas; Monteil, Caroline L.; Lefevre, Christopher T.
Summary: Obtaining high biomass yields of specific microorganisms for culture‐independent approaches is a challenge faced by scientists studying organism's recalcitrant to laboratory conditions and culture. This difficulty is highly decreased when studying magnetotactic bacteria (MTB) since their unique behaviour allows their enrichment and purification from other microorganisms present in aquatic environments. Here, we use Lake Pavin, a permanently stratified lake in the French Massif Central, as a natural laboratory to optimize collection and concentration of MTB that thrive in the water column and sediments. A method is presented to separate MTB from highly abundant abiotic magnetic particles in the sediment of this crater lake. For the water column, different sampling approaches are compared such as in situ collection using a Niskin bottle and online pumping. By monitoring several physicochemical parameters of the water column, we identify the ecological niche where MTB live. Then, by focusing our sampling at the peak of MTB abundance, we show that the online pumping system is the most efficient for fast recovering of large volumes of water at a high spatial resolution, which is necessary considering the sharp physicochemical gradients observed in the water column. Taking advantage of aerotactic and magnetic MTB properties, we present an efficient method for MTB concentration from large volumes of water. Our methodology represents a first step for further multidisciplinary investigations of the diversity, metagenomic and ecology of MTB populations in Lake Pavin and elsewhere, as well as chemical and isotopic analyses of their magnetosomes.